Polystyrene microplastics accelerated photodegradation of co-existed polypropylene via photosensitization of polymer itself and released organic compounds - Liu, Peng; Li, Huang; Wu, Jiajun; Wu, Xiaowei; Shi, Yanqi; Yang, Zeyuan; Huang, Kerang; Guo, Xuetao; Gao, Shixiang (Water research (Oxford), 2022)
•Photodegradation of polypropylene (PP) was accelerated by polystyrene (PS) microplastics.•Photosensitization of PS polymer itself and released organic compounds caused the critical effect.•The photodegradation of PP mediated by PS was controlled by ROS-involved mechanism.•OH• was the key contributor in combined system by PS itself and released organic compounds.•The duration of commercial PP box in real environment was shortened by co-existed PS. Combined pollution consisted of various types of microplastics (MPs) was extensively detected in the environment; however, little is known about their interaction on degradation behavior during exposure in sunlight. This study investigated the effects of polystyrene (PS) MPs and mechanisms on photodegradation of pure and commercial polypropylene (PP) MPs co-existed in aquatic environment. Results showed that PS MPs significantly accelerated photodegradation of co-existed PP, including faster oxidation and fragmentation. Photodegradation route of PP MPs such as the reaction priority of partial chemical bindings was even altered with the presence of PS MPs, highlighting the important role of PS in photodegradation process of PP. Analysis of leachate and free radical indicated that the critical effects were derived from photosensitization of PS polymer itself and its released dissolved organic matter (PS-DOM); here, more important role of PS itself in initial period and that of PS-DOM in later period. Among generated ROS, OH· was the key species for accelerating photodegradation of PP by PS itself and its released DOM, which were generated from the reaction of polymer radical with dissolved oxygen. The findings firstly reveal the important role of PS in photodegradation of co-existed MPs and suggested the shorter duration of (micro)plastics in combined system than that in the single, which provide useful information to assess environmental behavior and fate of MPs more holistically. [Display omitted]